Situasional Low Self Esteem Penyintas COVID-19: Studi Deskriptif - Eka Budiarto; Rita Rahayu; Ratnawati Ratnawati (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: This study aims to determine the description of situational low self-esteem that occurs in COVID-19 survivors.Methods: The method of this study used a quantitative descriptive design with a cross sectional approach. The study was conducted by online with the population are all Indonesian people who had suffered from COVID-19. The sampling technique used a total population. The measuring instrument used the State Self-Esteem Scale questionnaire. Data analysis used central tendency.Results:  This study found that the respondents health status related to COVID-19 100% of the respondents were COVID-19 survivors where the achievement of self-esteem scores was 72%.Conclusion:  Situational low self-esteem was occured in respondents with confirmed COVID-19